Organizational performance: The effect of supply chain management practices, supply chain responsiveness, and organizational capability - Harifi, Nindita (Journal of Management and Business Insight, 2024)
Purpose-Organizational performance is the main focus for every business person because it is related to facing globalization and competition. Globalization and business competition can be impacted if organizational performance can be maintained or continuously improved. Many factors affect organizational performance, both internal and external to the organization. This study analyzes the factors influencing organizational performance: supply chain management practices, supply chain responsiveness, and organizational capabilities. Design/Methodology/Approach-This study analyzes the performance of micro, small, and medium enterprises in the furniture sector in Yogyakarta, Indonesia. Based on a purposive sampling technique, a sample size of 60 respondents was obtained. The data obtained was then analyzed using Smart PLS software. Findings-The analysis results show that all three hypotheses of this study are accepted. Supply chain management practices are shown to affect organizational performance positively. Supply chain responsiveness is shown to have a positive effect on organizational performance. Organizational capability is shown to have a positive impact on organizational performance. Research limitations/implications-This research is limited to micro, small, and medium enterprises in the furniture sector in Yogyakarta, so the results of this study cannot be generalized to all business sectors. Each business sector certainly has its performance drivers, both internal and external to the organization. Originality/value-This study uses the object of micro, small, and medium enterprises in the furniture sector in Yogyakarta. This study uses an object that is different from other similar studies. In addition, previous studies also analyzed other factors that were not examined in this study.